Hubungan Konsumsi Fast Food, Aktivitas Fisik dan Durasi Tidur dengan Kejadian Obesitas pada Siswa di SMK Bina Am Ma’mur - Hanifah, Nida; Mustakim, Mustakim (J-Mestahat, 2024)
ABSTRACT Obesity is a global health problem caused by a lifestyle that includes inappropriate diet and physical activity levels. The purpose of this study was to determine the relationship between fast food consumption, physical activity and sleep duration with the incidence of obesity in students at Bina Am Ma'mur Vocational School in 2021. This study is a quantitative study using a cross sectional design. The results showed that there was a relationship between fast food consumption (P=0.000) and sleep duration (P=0.004) with the incidence of obesity in students at Bina Am Ma'mur Vocational School. It is recommended for schools to make promotive and preventive efforts, such as conducting counseling at school about the importance of choosing healthy foods, and others. Keywords: Obesity, Diet, Lifesyle, Students